A Novel Engagement-Pixel Tracking Method for Meshing Clearance Layout of Twin-Screw Rotors. (22nd September 2019) - Lu, Jie; Cai, Zhiqin; Cai, Sijie; Yao, Bin; Chen, Binqiang
Abstract : The performance of dry twin-screw compressors is primarily affected by the meshing clearance between a pair of meshing rotors. In this paper, a novel method for meshing clearance layout (MCL) is presented. The presented method is based on the engagement-pixel tracking (EPT) technique, which utilizes discrete-pixel curves generated by the two rotors. An algorithm for the proposed method is put forward. Firstly, when the profile of one rotor is known, the discrete point coordinates of the two rotor profiles and their thermal expansion profiles can be obtained. Secondly, the instantaneous contact models of the two rotors at special meshing positions are acquired under pixel coordinate system. Thirdly, through inspecting the pixels on the profile of a rotor and establishing the corresponding normal vector, the meshing clearance of the two rotors is extracted. Then, the meshing clearances can be generated by extracting the boundary pixels on the other rotor profile. Finally, the meshing clearance layout method is proposed. To verify the effectiveness of the presented method, a case study was conducted on a pair of meshing rotors to extract its meshing clearance. It was shown that the proposed method can be used as a tool for evaluating the clearance distribution of actual machined profiles.